2022
DOI: 10.1016/j.dcn.2021.101044
|View full text |Cite|
|
Sign up to set email alerts
|

Microstructural development from 9 to 14 years: Evidence from the ABCD Study

Abstract: During late childhood behavioral changes, such as increased risk-taking and emotional reactivity, have been associated with the maturation of cortico-cortico and cortico-subcortical circuits. Understanding microstructural changes in both white matter and subcortical regions may aid our understanding of how individual differences in these behaviors emerge. Restriction spectrum imaging (RSI) is a framework for modelling diffusion-weighted imaging that decomposes the diffusion signal from a voxel into hindered, r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
80
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 61 publications
(99 reference statements)
11
80
0
Order By: Relevance
“…In this study, we included ROI data from multiple modalities, yet high heterogeneity within ROIs has been reported, particularly within tracts and regions with the strongest age effects (77).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we included ROI data from multiple modalities, yet high heterogeneity within ROIs has been reported, particularly within tracts and regions with the strongest age effects (77).…”
Section: Discussionmentioning
confidence: 99%
“…RSI-Res PC2). Cortico-striatal connectivity appears to greatly develop during adolescence (Palmer et al, 2021), enabling integration between the striatum and the cortex, and possibly subserving cognitive control and value-guided action (Davidow et al, 2018). The relationship of PRS of psychiatric disorders and imaging components were weaker and mostly characterized by null and anecdotal evidence when examined separately for each imaging phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these disparate patterns of findings between late childhood and adulthood suggest sex-specific maturational trajectories during adolescence. Some prior work including adolescent samples has likewise suggested that sex differences may evolve over development (Clayden et al, 2012;Herting et al, 2017;Schmithorst et al, 2008;Seunarine et al, 2016;Simmonds et al, 2014 but see Lebel & Beaulieu, 2011), although sex-specific trajectories may not arise until after early adolescence (Palmer, Pecheva, et al, 2021). Sex differences in maturational trajectories between childhood and adulthood may be driven by pubertal development and the associated changes in sex hormones during adolescence (Crone & Dahl, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…These models were used as they allow for nested data structures while appropriately modeling non-independent data points, such as participants nested within MRI scanners; linear mixed-effects models have also been used extensively in previously published multi-scanner neuroimaging studies, including prior work in ABCD (e.g., Bohon & Welch, 2021;Hernandez et al, 2022;Pagliaccio, Durham, Fitzgerald, & Marsh, 2021;Palmer, Pecheva, et al, 2021;Palmer, Zhao, et al, 2021;Piccolo et al, 2016;Rapuano et al, 2020). All regressions for the current study were completed in R 3.6.1 using the lme4 package and included the following standard nuisance covariates as fixed effects: age, household income, parental education, race, and ethnicity; MRI scanner was modeled as a random effect in all analyses to adjust for scanner-related variability by modeling the hierarchical structure of our multi-scanner dataset (Bohon & Welch, 2021;Hernandez et al, 2022;Pagliaccio et al, 2021;Palmer, Pecheva, et al, 2021;Palmer, Zhao, et al, 2021;Rapuano et al, 2020). Results were considered significant and replicable if they survived a 5% false discovery rate (FDR) applied across the number of ROIs in the discovery cohort (q<0.05) and demonstrated p<0.05 in the replication cohort (Benjamini & Hochberg, 1995;Hernandez et al, 2022).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation